1973
DOI: 10.1159/000279822
|View full text |Cite
|
Sign up to set email alerts
|

Experimentelle Untersuchungen zur Löslichkeitsbeeinflussung mineralischer Harnkonkremente

Abstract: Although it is impossible to determine the occurrence of precipitation of solids in the urine tract, due to the statistical character of this process, the conditions of the resolution of the various minerals can be calculated exactly. Measurements of the solubility of calcium oxalate monohydrate as a function of the Mg, NaCl and citrate concentration of the urine prove the existence of complicated coupled chemical equilibriums. They cause magnesium salts to be ineffective in a resolution therapy of oxalate kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1975
1975
2005
2005

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Hammarsten's results [23] at 37 C are smooth; however, this author reported that her data were not consistent with the Debye-Hu Èckel law even at very low ionic strength. Knappwost and Matouschek's data [24] show a large scatter, some of them are lower and some are higher than the data from all other sources. The data of Ref.…”
Section: Commentioning
confidence: 79%
“…Hammarsten's results [23] at 37 C are smooth; however, this author reported that her data were not consistent with the Debye-Hu Èckel law even at very low ionic strength. Knappwost and Matouschek's data [24] show a large scatter, some of them are lower and some are higher than the data from all other sources. The data of Ref.…”
Section: Commentioning
confidence: 79%
“…All the papers have been scrutinised in the NEA organics review [7]. For the final data analysis only studies carried out in NaCl and KCl media with proper characterization of the solids in equilibrium with the solutions have been considered [8][9][10][11][12][13][14][15]. In all the above cases analytical equilibrium concentration data of dissolved calcium, oxalate, NaCl or KCl have been reported, and the aqueous speciation was recalculated in the NEA organics review [7] as follows.…”
Section: Calcium Oxalate Solubilitymentioning
confidence: 99%
“…The solubility of octocalcium phosphate drops by a factor of 3, if the urine pH is higher than 7 (17). Urea splitting bacteria for instance can shift the urine reaction into the alkaline region (18).…”
Section: We Think That In Immobilized Patientsmentioning
confidence: 99%